Caregiving styles and anxiety among couples: coping versus not coping with cardiac illness. Issue 1 (2nd January 2017) - George-Levi, Sivan; Vilchinsky, Noa; Rafaeli, Eshkol; Liberman, Gabriel; Khaskiaa, Abid; Mosseri, Morris; Hod, Hanoch
ABSTRACT: Background and Objectives : partners' caregiving efforts are not always beneficial to both recipient and provider. Bowlby's conceptualization of caregiving style as a stable predisposition may clarify such caregiving effects. The relationship between caregiving style (compulsive and sensitive) and anxiety among couples coping with cardiac illness and a matching control group not coping with cardiac illness were assessed. We hypothesized that one's compulsive caregiving would associate positively, and one's sensitive caregiving would associate negatively, with one's and one's partner's anxiety across contexts (cardiac and non-cardiac) and gender.Design : A comparative design of 131 couples with a diagnosis of husbands' acute cardiac syndrome and 68 matched couples in the community was applied.Methods : The Adult Caregiving Questionnaire and the Brief Symptoms Inventory were administered.Results : Structural equation modeling revealed that one's compulsive caregiving was positively associated with one's anxiety, across most contexts. Multi-group analyses revealed that the associations between one's compulsive caregiving and one's partner's anxiety levels differed depending on gender and context.Conclusions : The distress which emerges in an individual who takes on a caregiving role and in his/her partner seems to result not only from the demands of the concrete caregiving situation but also from one's and one's partner's developmental history.